Intervención del terapista respiratorio en paciente masculino de 60 años con diagnóstico de fibrosis pulmonar. - Santillán Bea, Jairo Jamphier (2022)
Pulmonary fibrosis is nothing more than a disease that affects the lower respiratory tract and its main characteristic and therefore the most important is the healing of the lung tissues, in this way the normal passage of air into the blood is considerably reduced, affecting the person who suffers from it. Among its main symptoms are dyspnea, dry cough and precordial pain, among others, and they vary from person to person. The damage caused by fibrosis in the lungs is irreversible, so the main objective of the treatment applied to patients with pulmonary fibrosis is to improve, reduce symptoms, and slow down the progression of the disease. Although some patients according to their requirement may opt for lung transplantation. Among the main risk factors is sex, since it affects the male sex more, and it is usually diagnosed more from 50 to 80 years of age. In some, the onset of the disease is gradual, it can occur over the course of months or years, in others its onset is rapid, presenting a serious picture of the disease. In certain patients, an acute exacerbation may occur, causing the condition to worsen rapidly, even requiring ventilatory support.